Molnupiravir or nirmatrelvir-ritonavir versus usual care in patients admitted to hospital with COVID-19 (RECOVERY): a randomised, controlled, open-label, platform trial - RECOVERY Collaborative Group; Horby, PW; Staplin, N; Peto, L; Emberson, JR; Campbell, M; Pessoa-Amorim, G; Basnyat, B; Thwaites, L; Van Doorn, R; Hamers, RL; Nel, J; et al. (2024)
Background: Molnupiravir and nirmatrelvir-ritonavir (Paxlovid) are oral antivirals that have been proposed as treatments for patients admitted to hospital with COVID-19. Methods: In this randomised, controlled, open-label, adaptive platform trial, several potential treatments for patients hospitalised with COVID-19 pneumonia were evaluated. Molnupiravir and nirmatrelvir-ritonavir were assessed in separate comparisons in RECOVERY, both of which are reported here. Eligible and consenting adults could join the molnupiravir comparison, the nirmatrelvir-ritonavir comparison, or both. For each comparison, participants were randomly allocated in a 1:1 ratio to the relevant antiviral (five days of molnupiravir 800mg twice daily or nirmatrelvir-ritonavir 300mg/100mg twice daily) or to usual care without the relevant antiviral drug, using web-based unstratified randomisation with allocation concealment. The primary outcome was 28-day mortality, and secondary outcomes were time to discharge alive from hospital, and among those not on invasive ventilation at baseline, progression to invasive ventilation or death. Analysis was by intention-to-treat. Both comparisons were stopped by the investigators because of low recruitment. ISRCTN (50189673) and clinicaltrials.gov (NCT04381936). Findings: From 24 January 2022 to 24 May 2023, 923 patients were recruited to the molnupiravir comparison (445 allocated molnupiravir and 478 allocated usual care), and from 31 March 2022 to 24 May 2023, 137 patients were recruited to the nirmatrelvir-ritonavir comparison (68 allocated nirmatrelvir-ritonavir and 69 allocated usual care). More than three-quarters of the patients in both comparisons were vaccinated and had anti-spike antibodies at randomisation, and more than two-thirds were receiving other SARS-CoV-2 antivirals (including remdesivir or sotrovimab). In the molnupiravir comparison, 74 (17%) patients allocated to molnupiravir and 79 (17%) patients allocated usual care died within 28 days (hazard ratio [HR] 0.93; 95% confidence interval [CI] 0.68-1.28; p=0.66). In the nirmatrelvir-ritonavir comparison, 13 (19%) patients allocated nirmatrelvir-ritonavir and 13 (19%) patients allocated usual care died within 28 days (HR 1.02; 95% CI 0.47-2.23; p=0.96). In neither comparison was there evidence of a significant difference in the duration of hospitalisation or the proportion of patients progressing to invasive ventilation or death. Interpretation: In adults hospitalised with COVID-19, neither molnupiravir nor nirmatrelvir-ritonavir were associated with reductions in 28-day mortality, duration of hospital stay, or risk of progressing to invasive mechanical ventilation or death although these comparisons had limited statistical power due to low recruitment. Funding: UK Research and Innovation (Medical Research Council) and National Institute of Health and Care Research (Grant ref: MC_PC_19056), and Wellcome Trust (Grant Ref: 222406/Z/20/Z). Trial registration: ClinicalTrials.gov NCT04381936 https://clinicaltrials.gov/ct2/show/NCT04381936